Islamic Animated Media as an Educational Tool: An Analysis of Islamic Educational Values in Nussa and Rara and Their Impact on Elementary School Students’ Religious Competence - Stefani Stefani; Karim Karim (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2026)
The rapid development of digital media has significantly influenced children’s learning patterns, including their understanding of religious values. However, the integration of Islamic educational values through animated media as a structured learning resource in elementary schools remains underexplored. This study aims to analyze the Islamic educational values contained in the animated film Nussa dan Rara Season 2 and examine its impact on the Islamic religious knowledge of fifth-grade students at SDN 2 Toronipa. The research employed a qualitative content analysis method to identify and categorize Islamic educational values presented in the film, complemented by descriptive analysis of students’ religious knowledge after exposure to selected episodes. The findings reveal that the film contains comprehensive Islamic educational values, including aqidah values (tauhid and faith in Allah), worship values (prayer and dhikr), and moral values (good manners, cleanliness, honesty, and asking permission). These values are conveyed through child-friendly narratives and contextual storylines that align with students’ daily experiences. Furthermore, the film demonstrates a positive impact on students’ understanding of tauhid concepts, motivation to perform worship practices, memorization of daily dhikr, and the development of positive religious attitudes. The study implies that educative and Islamic-oriented audio-visual media can serve as an effective alternative instructional strategy to strengthen religious competence in elementary education.